DOI: 10.18122/td/1776/boisestate
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Enjoyment, Anxiety, and Emotional Intelligence in Online Graduate Students' Self-Regulated Learning

Abstract: As online learning continues to grow, particularly amid the COVID pandemic, so too has interest among educational practitioners and researchers to understand the personal and contextual factors that shape students’ emotions in these environments. The control-value theory of achievement emotions has emerged as a useful framework for examining the antecedents and consequences of different emotions that students experience in online learning. The purpose of the present study was to validate the assumptions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
(208 reference statements)
0
1
0
Order By: Relevance
“…Prior studies have also shown that academic procrastination is more strongly correlated with negative emotions than positive emotions in remote settings (Henderikx et al, 2019; Rahimi & Vallerand, 2021). Third, enjoyment, in particular, has been selected by many studies to explore its role in relation to students' self‐regulatory processes in online learning environments (Artino & Jones, 2012; Henderikx et al, 2019; Touati, 2020; You & Kang, 2014). These studies have consistently shown that enjoyment is significantly correlated with students' adaptive and maladaptive self‐regulation in online learning environments.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have also shown that academic procrastination is more strongly correlated with negative emotions than positive emotions in remote settings (Henderikx et al, 2019; Rahimi & Vallerand, 2021). Third, enjoyment, in particular, has been selected by many studies to explore its role in relation to students' self‐regulatory processes in online learning environments (Artino & Jones, 2012; Henderikx et al, 2019; Touati, 2020; You & Kang, 2014). These studies have consistently shown that enjoyment is significantly correlated with students' adaptive and maladaptive self‐regulation in online learning environments.…”
Section: Methodsmentioning
confidence: 99%